Properties of alumina with RHA-reinforced aluminum composite using different sintering profile - Mohamad Aznan, M. N.; Mohamed Ariff, Azmah Hanim; Mohd Tahir, Suraya; Mazlan, Norkhairunnisa; As'arry, Azizan (Springer, 2017)
The purpose of this research is to study the effect of different sintering profiles on the properties of porous alumina ceramic composites. The mixtures of alumina, rice husk ash (RHA), aluminum, and sucrose binder solution were compacted and went through three different sintering profiles which involve two non-continuous procedures and one continuous procedure. In non-continuous, it involves two different profiles which are with and without pre-treated at 1000°C. To summarize, the three processing profiles used for this study were (S1) non-continuous (without 1000°C), (S2) non-continuous (with 1000°C), and (S3) continuous (with 1000°C). Results from this study show that S2 gives better properties than S1 and S3. From microstructure evaluation, S2 provided lower total porosity. Mechanical properties also revealed that the sintering linear shrinkage measured for S2 has the highest value (2.38%) which results in the highest density (1.43 g/cm3), lowest total porosity (48.05%), and the highest tensile strength (9.26 MPa).